(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2012)
This work was carried out on the lake Chongón, Guayas, located at Km 26 of the route to the coast, west of Chongón, with a geographic position of 02 º 13’08 .61’’ S and 80 ° 07’31 .86’’ W. There were four field trips during the months of December 2011 and April 2012. Zooplankton samples were obtained at eight stations, four of which were located in the littoral zone and four in the limnetic zone. We found 12 species of cladocerans, belonging to 11 genera and 7 families: Chydorus sphaericus Müller, 1785; Kurzia latissima Kurz, 1874; Leydigiopsis brevirostris Brehm, 1938; Alonella nana Baird, 1843; Bosmina longirostris OF Müller, 1776, Moina micrura Kurz, 1874; Ceriodaphnia cornuta Sars, 1885; Simocephalus vetulus OF Müller, 1776; Simocephalus acutifrons Johnson, 1954; Diaphanosoma brachyurum Liévin, 1848; Ilyocryptus spinifer Herrick, 1882 and Drepanothrix dentata Eurén, 1861. The diversity index was high, with H ’= 2.2440 bits and evenness of E = 0.6259. Diversity index for littoral and limnetic zones show a significant difference in favor of the littoral zone with a value of H ’= 2.7228 bits and evenness of E = 0.8197 versus H’ = 0.3169 and E = 0.0916 bits for the limnetic zone. This confirms the hypothesis that the coastal area has a higher density and diversity of cladocerans.